Satisfaction Survey: Use of Facilities, Buildings and Grounds Cleanliness, Communication System and Delivery of Supply in Bulacan State University, Malolos, Bulacan - Estacio, Dennis; Gopez, Ma. Teresa (Future Science / FSH-PH Publications, 2021)
The study aims to define the respondent’s level of satisfaction with the facilities management services at Bulacan State University. Specifically, this study sought to answer the research question: What is the satisfaction level of the personnel at Bulacan State University in terms of; a. Use of school facilities; b. Campus and building grounds cleanliness; c. Availability of communication system in the campus; and d. Requisition and deliveries of supplies. This study utilized the Descriptive Research through survey method to obtain data and information needed in determining the extent of the satisfaction level of the respondents on the efficiency of the support services in the university. Based from the results of the study, the researchers have drawn the following conclusions: 1. the satisfaction level of the administrators, non-teaching personnel, and faculty members in the existing procedures on the use of school facilities was satisfied, less satisfied in the cleanliness of the comfort rooms, less satisfied in the timely delivery of supplies, thus resulting to low level of respondent’s satisfaction. On the other hand, majority of the respondents were satisfied with the communication system within the campus but less satisfied with the way that the communication letters/memoranda are being cascaded properly down to the last concerned personnel.